Effects of different light intensity on leaf color changes in a Chinese cabbage yellow cotyledon mutant - Huo, Jianyu; Zhang, Ninan; Gong, Ying; Bao, Yongrong; Li, Yinyin; Zhang, Lugang; Nie, Shanshan (Frontiers in Plant Science, 2024)
Leaf color is one of the most important phenotypic features in horticultural crops and directly related to the contents of photosynthetic pigments. Most leaf color mutants are determined by the altered chlorophyll or carotenoid, which can be affected by light quality and intensity. Our previous study obtained a Chinese cabbage yellow cotyledon mutant that exhibited obvious yellow phenotypes in the cotyledons and the new leaves. However, the underlying mechanisms in the formation of yellow cotyledons and leaves remain unclear. In this study, the Chinese cabbage yellow cotyledon mutant 19YC-2 exhibited obvious difference in leaf color and abnormal chloroplast ultrastructure compared to the normal green cotyledon line 19GC-2. Remarkably, low-intensity light treatment caused turn-green leaves and a significant decrease in carotenoid content in 19YC-2. RNA-seq analysis revealed that the pathways of photosynthesis antenna proteins and carotenoid biosynthesis were significantly enriched during the process of leaf color changes, and many differentially expressed genes related to the two pathways were identified to respond to different light intensities. Remarkably, BrPDS and BrLCYE genes related to carotenoid biosynthesis showed significantly higher expression in 19YC-2 than that in 19GC-2, which was positively related to the higher carotenoid content in 19YC-2. In addition, several differentially expressed transcription factors were also identified and highly correlated to the changes in carotenoid content, suggesting that they may participate in the regulatory pathway of carotenoid biosynthesis. These findings provide insights into the molecular mechanisms of leaf color changes in yellow cotyledon mutant 19YC-2 of Chinese cabbage.